2020
DOI: 10.3390/cells9122679
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Autophagy as a Strategy for Treating COVID-19

Abstract: Currently, an efficient treatment for COVID-19 is still unavailable, and people are continuing to die from complications associated with SARS-CoV-2 infection. Thus, the development of new therapeutic approaches is urgently needed, and one alternative is to target the mechanisms of autophagy. Due to its multifaceted role in physiological processes, many questions remain unanswered about the possible advantages of inhibiting or activating autophagy. Based on a search of the literature in this field, a novel anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 231 publications
(259 reference statements)
0
59
0
Order By: Relevance
“…Based on its autophagy/mitophagy induction activity, its potential application in the treatment of other diseases also deserves to be explored. Under certain conditions, the activation of autophagy may serve as a treatment strategy to defend against intracellular bacteria, parasites and virus infection by targeting intracellular microorganisms (xenophagy) and mediating the clearance of microorganisms or via modulating the antiviral immune response of organisms to defend against infection [ 44 ]. In terms of anti-infection, whether CVB-D possesses potential applications is largely unknown and deserves to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Based on its autophagy/mitophagy induction activity, its potential application in the treatment of other diseases also deserves to be explored. Under certain conditions, the activation of autophagy may serve as a treatment strategy to defend against intracellular bacteria, parasites and virus infection by targeting intracellular microorganisms (xenophagy) and mediating the clearance of microorganisms or via modulating the antiviral immune response of organisms to defend against infection [ 44 ]. In terms of anti-infection, whether CVB-D possesses potential applications is largely unknown and deserves to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, autophagy dysfunctions are often associated with inflammatory and autoimmune diseases [44] and innate immune responses and inflammation, crucial in anti-viral responses, are regulated by autophagy [54]. Several studies have shown that many viruses, like coronaviruses, have evolved strategies to evade the host response by directly hijacking the autophagy pathway in support of their life cycle and spread or by disrupting the host control on the production of anti-viral cytokines [54][55][56]. Host genetics also contributes to aberrant immunity in autoimmune diseases and susceptibility to infectious diseases in humans and such variants are often found in genes involved in the immune response and inflammation [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin reduces oxidative stress, reinforces UPR, and unlocks the autophagy blockage caused by the virus, allowing autophagosome maturation and a decrease in double-membrane vesicle formation and viral replication capacity [ 55 ]. Moreover, photothermal therapy could enhance ROS production, which is shown to downregulate the Akt-mTOR-p70S6K pathway, resulting in autophagy [ 153 ].…”
Section: Viral Infection and Autophagymentioning
confidence: 99%